2011
DOI: 10.2215/cjn.04250510
|View full text |Cite
|
Sign up to set email alerts
|

FGF-23 as a Predictor of Renal Outcome in Diabetic Nephropathy

Abstract: SummaryBackground and objectives Fibroblast growth factor 23 (FGF-23) has emerged as a new factor in mineral metabolism in chronic kidney disease (CKD). An important regulator of phosphorus homeostasis, FGF-23 has been shown to independently predict CKD progression in nondiabetic renal disease. We analyzed the relation between FGF-23 and renal outcome in diabetic nephropathy (DN).Design, setting, participants, & measurements DN patients participating in a clinical trial (enalaprilϩplacebo versus enalaprilϩlosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 28 publications
5
90
1
7
Order By: Relevance
“…For example, hyperphosphatemia, high serum parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23) levels, and vitamin D deficiency were reported to be risk factors for mortality and cardiovascular events in patients with CKD, especially in dialysis patients (2)(3)(4)(5)(6)(7). Recently, these derangements were reported to be associated with CKD progression (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, hyperphosphatemia, high serum parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23) levels, and vitamin D deficiency were reported to be risk factors for mortality and cardiovascular events in patients with CKD, especially in dialysis patients (2)(3)(4)(5)(6)(7). Recently, these derangements were reported to be associated with CKD progression (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting result is that hyperphosphatemia occurred only in 12% of the patients, all of whom had glomerular filtration rate lower than 30 mL/min. 44 Clinical studies have shown an association of high FGF-23 levels and CKD progression, 45,46 development of severe secondary hyperparathyroidism, 47 left ventricle hypertrophy, 48 and mortality. 49 A recent study with 177 nondiabetic patients with serum creatinine ranging from 0.9 to 4.9 mg/dL, followed up for a mean period of 53 months, has reported that FGF-23 was a predictor of the progression of renal disease as important as glomerular filtration rate.…”
Section: Fgf-23 and Clinical And Experimental Studiesmentioning
confidence: 99%
“…45 In another study with 55 patients with stage III diabetic nephropathy with macroalbuminuria followed up for a mean period of 30.7 months, the FGF-23 level was also an isolated predictive factor for the evolution of diabetic nephropathy, regardless of the levels of P, Ca, PTH, and 25(OH) 2 D 3 . 46 The hypothesis that high FGF-23 levels are associated with secondary hyperparathyroidism has been demonstrated in a study with 103 patients undergoing hemodialysis. By the end of two years, patients who had high FGF-23 levels at the beginning of the study developed more severe forms of secondary hyperparathyroidism, independently of the initial PTH levels.…”
Section: Fgf-23 and Clinical And Experimental Studiesmentioning
confidence: 99%
See 2 more Smart Citations